State of the art in designing an effective topical formulation - Ab. Hadi, Hazrina (2014)
Common belief in topical formulation is about 60% of the active is absorbed without putting into consideration the excipients in the formulation. Despite of effectiveness of an active in exerting its cosmeceutical and pharmaceutical effects, adequate formulations for the active still need to be designed for successful delivery to the target sites. This is because skin delivery system is associated with a major drawback, which is that only small amounts (about 1%) of actives are effectively delivered through the skin which may be due to several factors, such as (a) drug metabolism by bacteria in the skin, (b) metabolic enzymes in the skin, (c) difficulties in maintaining contact between a device and the skin, (d) difficulty in passing the skin barrier i.e. the stratum corneum. Using chemical penetration enhancers is one of the strategies that can be used to modulate the skin barrier to deliver the active compound effectively. Hence, it is important to understand the role of the excipients in the formulations which include their mode of actions and their residence time in the formulations. The effect of the excipients on the permeation can be evaluated with infinite dose permeation studies using Franz diffusion cells. Infinite dose studies are based on Fick’s first law. Therefore, any enhancement effect achieved by selected solvents should be due to the alteration of the parameters laid out in Fick’s first law. When permeation enhancement occurs, it may be due to: 1) Increasing the concentration of the drug at the skin surface 2) Increasing the amount of the drug which partitions into the stratum corneum 3) Altering the diffusion coefficient 4) Decreasing the diffusional pathway Diffusion is mainly driven by the concentration gradient. Fick’s law states that the flux should increase linearly as the concentration is increased and should reach a maximum when the solubility limit is reached. Therefore, solubility data are useful when designing formulations since permeation is a passive process as described by Fick’s first law of diffusion. Biophysical study to investigate the macrospic changes on the skin can be carried out using Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) scans. This is because stratum corneum consists of keratin filaments which are embedded in a lipid matrix. These lipids are important in maintaining the skin barrier. Therefore, by evaluating the changes in the molecular organization of the stratum corneum lipids, the effects of topical formulations on the skin barrier can be investigated. The ATR-FTIR should give further insight into how the formulations affect the total lipid and fatty acid content of the skin.